Preliminary study on parasitism of aphids (Hemiptera: Aphididae) in relation to characteristics of alfalfa fields (Medicago sativa L.) in the Argentine Pampas - Zumoffen, Leticia; Salto, Cesar Eduardo; Salvo, Silvia Adriana (Elsevier, 2019)
Alfalfa is a perennial crop and is one of the most relevant forage resources for cattle in the Argentine Pampas, with aphids (Hemiptera Aphididae), one of the main pest insects in alfalfa, being frequently attacked by a rich fauna of aphidiinae parasitoids (Hymenoptera: Braconidae). The aim of this study was to identify the possible field characteristics that influence the parasitism rates of aphids in alfalfa, in order to recommend simple methods of environmental manipulation to enhance the action of parasitoids. The abundance of aphids and their parasitism were estimated fortnightly, over a period of seven months in fourteen alfalfa fields located near the city of Rafaela, Santa Fe, through the collection of stem cuttings. The influence of field size, age of crop, and percentage of borders with spontaneous vegetation, on aphid abundance and their parasitism rates, were assessed through general lineal models with repeated measures. Greater aphid populations were observed in fields with a low percentage of natural borders, whereas the impact by parasitoids was higher in older crops and in those fields with a high percentage of natural borders. The relative importance of the characteristics of fields on parasitism of aphids is discussed, bearing in mind that conservation is the strategy of biological control recommended for developed countries given its low cost and potential sustainability.